2017
DOI: 10.1088/1757-899x/225/1/012101
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Heat Transfer Characteristics of Automobile Radiator using TiO2-Nanofluid Coolant

Abstract: Abstract:The use of nanoparticle dispersed coolants in automobile radiators improves the heat transfer rate and facilitates overall reduction in size of the radiators. In this study, the heat transfer characteristics of water/propylene glycol based TiO 2 nanofluid was analyzed experimentally and compared with pure water and water/propylene glycol mixture. Two different concentrations of nanofluids were prepared by adding 0.1 vol. % and 0.3 vol. % of TiO 2 nanoparticles into water/propylene glycol mixture (70:3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Salamon et al [19] analyzed experimentally the heat transfer characteristics of a car radiator using PG/W-based TiO 2 nanofluid as a coolant. The nanofluids were prepared by dispersing 0.1 and 0.3 vol.% of TiO 2 nanoparticles into a 30:70 PG/W under different operating temperatures within the range [50-80 • C].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salamon et al [19] analyzed experimentally the heat transfer characteristics of a car radiator using PG/W-based TiO 2 nanofluid as a coolant. The nanofluids were prepared by dispersing 0.1 and 0.3 vol.% of TiO 2 nanoparticles into a 30:70 PG/W under different operating temperatures within the range [50-80 • C].…”
Section: Resultsmentioning
confidence: 99%
“…Among these methods, nanofluids have proven to be an effective way to achieve that objective without increasing the size, cost, and complexity of thermal equipments too much. Ethylene-and propylene-glycol-based nanofluids have been then widely considered for their applications, mainly to remove heat in car radiators [9][10][11][12][13][14][15][16][17][18][19][20][21], diesel electric generators [22], industrial heat exchangers [23], and electronic devices [24,25]. General reviews on nanofluids have been published so far in the literature focusing on the preparation and stability of nanofluids [26,27], on the synthesis, thermo-physical properties, and heat transfer mechanisms of nanofluids [28], or on their applications in heat exchangers [29].…”
Section: Introductionmentioning
confidence: 99%
“…It is also observed that initially at a lower operating temperature the water depicts a marginally higher heat removal factor than nanofluids this was due to low density and the high specific heat of water. As the fluid temperature increases, the density of the nanofluids decreases and contact of nanoparticles with the surface of absorber increases [28], which leads to improvement in heat exchanger performance. Therefore, the heat removal factor for the nanofluidbased PV/T system decreases at a slower rate with increase in inlet fluid temperature.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the heat transfer coefficients first increased, and then decreased with the increase in volumetric concentrations of all nanofluids. Salamon et al experimentally examined the thermal performance of a 70/30 water/PG-based nanofluid with 0.1% and 0.2% TiO 2 concentration in an automobile radiator and compared it with the performance of water and water/PG mixtures [22]. They found that the heat rejection rate obtained with PG was higher than that yielded by the nanofluid at low coolant inlet temperatures.…”
Section: Introductionmentioning
confidence: 99%